Robot Car Arduino Ultrasonic Sensor HC-SR04 Dengan Metode Fuzzy Logic Controller - Adie Kusna Wibowo; Ibnu Triyanto (LPPM STMIK AL MUSLIM, 2024)
The navigation system is one of the main components required on mobile robots for obstacle avoidance. One application of the navigation system on robots is by using the HC SR04 ultrasonic sensor. The HC SR04 ultrasonic sensor can detect various types of obstacles around it by measuring the distance between the sensor and the objects. To achieve good results, ultrasonic sensors are used to measure the distance of obstacles on the left, front, and right sides of the robot. The mobile robot used is a wheeled robot designed with a differential wheel steering system powered by a DC motor actuator. An Arduino Nano is used as the control system for the mobile robot obstacle avoidance, employing the fuzzy logic controller method as a problem-solving control system methodology that is suitable for implementation in the system, determining the robot's turning angle The variables used to determine the turning angle are the distances measured by the left, front, and right sensors. With this distance database, a decision tree is generated from the training process using the backtracking algorithm. The decision tree contains rules for the robot's turning angles, specifically 30°, 60°, and 90° to the left and right. The testing process is conducted by applying the decision tree rules to the robot, then operating the robot at a certain speed on a wall obstacle course with predetermined turning angles. Through testing results on the mobile robot obstacle avoidance, an accuracy of 90% is achieved for the robot's turning angle